Adhesion of Trypanosoma cruzi trypomastigotes to fibronectin or laminin modifies tubulin and paraflagellar rod protein phosphorylation. - Eliciane C Mattos; Robert I Schumacher; Walter Colli; Maria Julia M Alves (PLoS ONE, 2012)
BACKGROUND: The unicellular parasite Trypanosoma cruzi is the causative agent of Chagaś disease in humans. Adherence of the infective stage to elements of the extracellular matrix (ECM), as laminin and fibronectin, is an essential step in host cell invasion. Although members of the gp85/TS, as Tc85, were identified as laminin and fibronectin ligands, the signaling events triggered on the parasite upon binding to these molecules are largely unexplored. METHODOLOGY/PRINCIPAL FINDINGS: Viable infective parasites were incubated with laminin, fibronectin or bovine serum albumin for different periods of time and the proteins were separated by bidimensional gels. The phosphoproteins were envisaged by specific staining and the spots showing phosphorylation levels significantly different from the control were excised and identified by MS/MS. The results of interest were confirmed by immunoblotting or immunoprecipitation and the localization of proteins in the parasite was determined by immunofluorescence. Using a host cell-free system, our data indicate that the phosphorylation contents of T. cruzi proteins encompassing different cellular functions are modified upon incubation of the parasite with fibronectin or laminin. CONCLUSIONS/SIGNIFICANCE: Herein it is shown, for the first time, that paraflagellar rod proteins and α-tubulin, major structural elements of the parasite cytoskeleton, are predominantly dephosphorylated during the process, probably involving the ERK1/2 pathway. It is well established that T. cruzi binds to ECM elements during the cell infection process. The fact that laminin and fibronectin induce predominantly dephosphorylation of the main cytoskeletal proteins of the parasite suggests a possible correlation between cytoskeletal modifications and the ability of the parasite to internalize into host cells.